1995
DOI: 10.1111/j.1550-7408.1995.tb05906.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Subunit Ribosomal DNA Phylogeny of Various Microsporidia with Emphasis on AIDS Related Forms

Abstract: Phylogenetic analysis of the small subunit ribosomal DNA of a broad range of representative microsporidia including five species from humans (Enterocytozoon bieneusi, Nosema corneum, Septata intestinalis, Encephalitozoon hellem and Encephalitozoon cuniculi), reveals that human microsporidia are polyphyletic in origin. Septata intestinalis and E. hellem are very similar to the mammalian parasite E. cuniculi. Based on the results of our phylogenetic analysis, we suggest that S. intestinalis be designated Encepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
112
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(120 citation statements)
references
References 25 publications
7
112
1
Order By: Relevance
“…After germination, the emptied content of the spores was used for DNA extraction by standard phenol-chloroform method. The 16S small subunit (SSU) rRNA gene was amplified using the primers 18f 5k-CACCAG-GTTGATTCTGCC-3k and 1537r 5k-TTATGA-TCCTGCTAATGGTTC-3k designed by Baker et al (1995). PCR amplification was carried out in 200 ml microfuge tubes, using 10 ng DNA, 5 pmol of each primer, 0 .…”
Section: Isolation Of Dna Pcr Amplification and Sequencing Of 16s Ssmentioning
confidence: 99%
“…After germination, the emptied content of the spores was used for DNA extraction by standard phenol-chloroform method. The 16S small subunit (SSU) rRNA gene was amplified using the primers 18f 5k-CACCAG-GTTGATTCTGCC-3k and 1537r 5k-TTATGA-TCCTGCTAATGGTTC-3k designed by Baker et al (1995). PCR amplification was carried out in 200 ml microfuge tubes, using 10 ng DNA, 5 pmol of each primer, 0 .…”
Section: Isolation Of Dna Pcr Amplification and Sequencing Of 16s Ssmentioning
confidence: 99%
“…It was first recognized in 1857 by NĂ€geli (2). Recently, phylogenetic analyses based on conserved proteins (3)(4)(5), ribosomal DNA (rDNA) sequences (6,7), and complete sequencing of the Encephalitozoon cuniculi genome (8) have suggested that microsporidia, which undergo a highly reductive evolution, are closely related to fungi (9). However, the N. bombycis genome has greatly expanded due to transposable elements and gene duplications (10).…”
mentioning
confidence: 99%
“…intestinalis (formerly Septata intestinalis) -this pathogen was first described by Cali et al (1991b) found in patients with chronic diarrhea, by Orenstein et al (1992) in a case of disseminated microsporidiosis and from humans infecting enterocytes, macrophages and associated with diarrhea in an Aids patient. This result was underlined by the analysis of Baker et al (1995) who suggest that S. intestinalis should be designated as E. intestinalis on the basis of the phylogenetic analysis of the small subunit ribosomal DNA. This parasite was found associated with chronic diarrhea and dissemination in Aids patients (Cali et al 1993), small intestinal microsporidiosis (Field et al 1993).…”
Section: Encephalitozoonmentioning
confidence: 93%